Penegakan Hukum Kelembagaan Ketenagakerjaan Terhadap Pengawasan Tenaga Kerja Asing Di Kota Tangerang Selatan - Alvan Ridwan; Indra Rahmatullah (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2019)
Abstract:This study aims to explain the Law Enforcement of Supervision of Foreign Workers by the Tangerang Regional Supervision Agency 2 Based on Law No. 13 of 2003 concerning Labor in the City of South Tangerang. This study uses qualitative research using an empirical normative research approach. This study conducted a review of the laws and regulations, books, and journals (library research) that are directly related to this research. The researcher also conducts direct field research by observing and interviewing relevant parties, namely the Tangerang Regional Supervision Region 2. The results of the study indicate that there are still foreign workers who violate the applicable provisions stipulated in Article 42 to Article 49 concerning the Use of Foreign Workers Act Number 13 of 2003 concerning Manpower and the insufficient number of supervisors of the Tangerang 2 Regional Supervision Agency to supervise companies in the City of South Tangerang to carry out supervision in accordance with Law Number 13 of 2003 concerning Manpower.Keywords: Law Enforcement, Supervision, Foreign Workers